1999
DOI: 10.1046/j.1471-4159.1999.731749.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C and the Opposite Regulation of Sodium Channel α‐ and β1‐Subunit mRNA Levels in Adrenal Chromaffin Cells

Abstract: Our previous [3 H]saxitoxin binding and 22 Na influx assays showed that treatment of cultured bovine adrenal chromaffin cells with 12-O-tetradecanoylphorbol 13-acetate (TPA) or phorbol 12,13-dibutyrate (PDBu), an activator of protein kinase C (PKC), decreased the number of cell surface Na channels (IC 50 ϭ 19 nM) but did not alter their pharmacological properties; Na channel downregulation developed within 3 h, reached the peak decrease of 53% at 15 h, and was mediated by transcriptional/translational events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 66 publications
7
37
0
Order By: Relevance
“…Plasmids containing hNE-Na cDNA, and rat brain Na ϩ channel ␤ 1 -subunit cDNA were generously donated by Drs. F. Hofmann (Technischen Universitä t Mü nchen) and Y. Oh (University of Alabama), respectively Yanagita et al, 1999Yanagita et al, , 2000Shiraishi et al, 2001a,b).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Plasmids containing hNE-Na cDNA, and rat brain Na ϩ channel ␤ 1 -subunit cDNA were generously donated by Drs. F. Hofmann (Technischen Universitä t Mü nchen) and Y. Oh (University of Alabama), respectively Yanagita et al, 1999Yanagita et al, , 2000Shiraishi et al, 2001a,b).…”
Section: Methodsmentioning
confidence: 99%
“…Isolated bovine adrenal chromaffin cells were cultured (4 ϫ l0 6 /dish, Falcon; 35 mm in diameter) under 5% CO 2 /95% air in a CO 2 incubator in Eagle's minimum essential medium containing 10% calf serum and 3 M cytosine arabinoside to suppress the proliferation of nonchromaffin cells (Yanagita et al, , 1999(Yanagita et al, , 2000. The cells were exposed to normal fresh medium or serum-free fresh medium (serum deprivation treatment) or treated without or with PD98059 or U0126 in normal fresh medium for up to 48 h, 3 days after plating.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ML7 directly targets the myosin light chain kinase pathway by inhibiting its activity (23). Phorbol 12,13-dibutyrate, on the other hand, activates the protein kinase C (24,25) and therefore increases myosin II activity. So far, there exists a range of data on mechanical property measurements of adherent cells treated with these drugs (26)(27)(28)(29), which have shown that inhibition of myosin activity leads to a loss of cell prestress and a subsequent lower measured elastic modulus of the cells.…”
Section: Introductionmentioning
confidence: 99%